GluN2D subunit-containing NMDA receptors regulate reticular thalamic neuron function and seizure susceptibility - Dinesh Y. Gawande; Gajanan P. Shelkar; Kishore Kumar S. Narasimhan; Jinxu Liu; Shashank M. Dravid (Neurobiology of Disease, 2023)
Thalamic regulation of cortical function is important for several behavioral aspects including attention and sensorimotor control. This region has also been studied for its involvement in seizure activity. Among the NMDA receptor subunits GluN2C and GluN2D are particularly enriched in several thalamic nuclei including nucleus reticularis of the thalamus (nRT). We have previously found that GluN2C deletion does not have a strong influence on the basal excitability and burst firing characteristics of reticular thalamus neurons. Here we find that GluN2D ablation leads to reduced depolarization-induced spike frequency and reduced hyperpolarization-induced rebound burst firing in nRT neurons. Furthermore, reduced inhibitory neurotransmission was observed in the ventrobasal thalamus (VB). A model with preferential downregulation of GluN2D from parvalbumin (PV)-positive neurons was generated. Conditional deletion of GluN2D from PV neurons led to a decrease in excitability and burst firing. In addition, reduced excitability and burst firing was observed in the VB neurons together with reduced inhibitory neurotransmission. Finally, young mice with GluN2D downregulation in PV neurons showed significant resistance to pentylenetetrazol-induced seizure and differences in sensitivity to isoflurane anesthesia but were normal in other behaviors. Conditional deletion of GluN2D from PV neurons also affected expression of other GluN2 subunits and GABA receptor in the nRT. Together, these results identify a unique role of GluN2D-containing receptors in the regulation of thalamic circuitry and seizure susceptibility which is relevant to mutations in GRIN2D gene found to be associated with pediatric epilepsy.